Comparison between Crossfit training and Tabata training effect on lung capacity / Nur Syairah Karim - Karim, Nur Syairah (Faculty of Sport Science and Recreation, 2017)
The purpose of this study is to compare the effect of lung capacity between CrossFit training and Tabata training. The lung capacity parameters that are measured are Force Vital Capacity (FVC), Force Expiratory Flow (FEF), Peak Expiratory Flow (PEF) and Force Expiratory Volume 25% - 75% (FEV 25% - 75%). 20 subject from UMP Footballer were divided by two group which is 10 subject for Crossfit training and 10 subjects for Tabata training. All subjects were testing using spirometer before and after 6-week training intervention. The result and data collected were analysed by using Statistical Package for Social Science (SPSS) version 19.0. The lung capacity testing result was analysed using Paired T test. The result shows there is no significance difference of FVC, FEF, PEF and FEV 25% - 75% between CrossFit training and Tabata training. The p-value for FVC, FEF, PEF and FEV 25% - 75% is greater than 0.05.